INCREASING CALCIUM OXIDE (CaO) TO ACCELERATE MOULTING AND SURVIVAL RATE VANNAMEI SHRIMP (Litopenaeus vannamei)) - Gito Erlando; Rusliadi '; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research about the increasing Calcium Oxide (CaO) to accelerate moulting and survival rate vannamei shrimp (Litopenaeus vannamei) was conducted from Agustus until September 2015 at Balai Perikanan Budidaya Air Payau, Instalasi Pembenihan Udang (IPU) Gelung, Situbondo Provinsi Jawa Timur. The purpose of this research was to investigate optimum doses calcium oxide to accelerate moulting and the survival rate vannamei shrimp (Litopenaeus vannamei). Vannamei shrimp with size PL25 were used in the research. The stoples that used 25L and filled with water 20L. The treatment given is giving of calcium oxide with different doses namely dose of 25mg, 50mg, 75mg, 100mg and added with the control treatment. This research uses Complete Randomized Design (CRD) with 1 factor 3 levels and 3 replication. Calcium Oxide (CaO) with doses of 75mg can produce intensity of moulting 43 times and survival rate vannamei shrimp (Litopenaeus vannamei) of 85%.Keywords: Calcium Oxide, Vannamei shrimp, moulting, survival rate